2021
DOI: 10.1371/journal.pone.0255137
|View full text |Cite
|
Sign up to set email alerts
|

Shift of bacterial communities in heavy metal-contaminated agricultural land during a remediation process

Abstract: Anthropogenic activities accompanied by heavy metal waste threaten the environment. Heavy metal pollution alters the soil microbial community composition, and the microorganisms that adapt to this stress increase in abundance. The remediation process of contaminated soil not only reduces the concentration of heavy metals but also alters the bacterial communities. High-throughput 16S rDNA sequencing techniques were applied to understand the changes in soil microbial communities. Using the remediation approach o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…We expected to find a higher diversity in the neutral-pH zones (zones 1, 5, and 6), since other studies had previously reported that neutral-pH environments exhibit greater bacterial diversity when compared to with acidic soil environments, such as those of zones 2, 3, and 4 ( Fierer and Jackson, 2006 ; Xiao et al, 2021 ). In terms of representation, there was an overrepresentation of the Pseudomonadaceae family in the six zones, an expected result considering previous results from different heavy metal soil samples, including mine tailings ( Gagnon et al, 2020 ; Huang et al, 2021 ). The relative abundance of the Erwiniaceae family differed between zones, having a higher abundance in zones 2, 3, and 4 (old tailings).…”
Section: Resultssupporting
confidence: 65%
“…We expected to find a higher diversity in the neutral-pH zones (zones 1, 5, and 6), since other studies had previously reported that neutral-pH environments exhibit greater bacterial diversity when compared to with acidic soil environments, such as those of zones 2, 3, and 4 ( Fierer and Jackson, 2006 ; Xiao et al, 2021 ). In terms of representation, there was an overrepresentation of the Pseudomonadaceae family in the six zones, an expected result considering previous results from different heavy metal soil samples, including mine tailings ( Gagnon et al, 2020 ; Huang et al, 2021 ). The relative abundance of the Erwiniaceae family differed between zones, having a higher abundance in zones 2, 3, and 4 (old tailings).…”
Section: Resultssupporting
confidence: 65%
“…In situ bioremediation uses naturally occurring bacteria to degrade contaminants in soil or water. In ex situ bioremediation, polluted soil is located in a lined above-ground treatment area of an indigenous microbial community [ 143 , 144 ].…”
Section: Methods Of Bioremediationmentioning
confidence: 99%
“…The feature analysis of the NGS library showed Proteobacteria with a high frequency in all the samples irrespective of the arsenic components, which can be explained by the resistance or the tolerance mechanisms of Proteobacteria [12]. Numerous studies found Proteobacteria to be the main phylum [31-33]. The present study found Bacteroidetes to be the main phylum in the TDE.…”
Section: Discussionmentioning
confidence: 50%